Impact of Uncertainty on Central Bank Digital Currency (CBDC) Development at Different Country Income Levels - Prayudya, Daffa Rizqi; Firmansyah (Economy of Regions, 2025)
The drawbacks of cryptocurrencies have prompted central banks to explore central bank digital currencies (CBDCs) as a new means of payment. However, various uncertainties may hinder the optimal design and implementation of CBDCs. This study examines the impact of uncertainty on CBDC development across countries with different income levels. Using data from 92 countries spanning 2014 to 2021, the research employs Ordered Logit and Probit models to analyse categorized dependent variables reflecting CBDC development, followed by an Ordinary Least Squares (OLS) with fixed effects model as a robustness check. Subsample estimations are applied to assess the effects within high, middle, and low-income countries. The study finds that uncertainty significantly and negatively impacts CBDC development, with the effect being more pronounced in middle and low-income countries. This suggests that the underdeveloped interoperability of the financial system, along with insufficient infrastructure and digital literacy, are key factors delaying CBDC progress in these regions, particularly when uncertainty is high. Collaboration and information-sharing among central banks are crucial to reduce global uncertainty and share best practices. Central banks should also prioritize the development of transparent regulatory frameworks, enhance digital literacy, and implement targeted infrastructure development incentives. Future research should focus on identifying optimal CBDC designs tailored to each income level to overcome these obstacles and foster a more inclusive and resilient financial ecosystem.